Association between lactobacillus levels, depressive mood, and BMI in college students: the moderating role of physical activity - Wu, Youliang; Yi, Qing; Qi, Zihan; Yin, Yao; Qi, Yufei (Frontiers in Nutrition, 2025)
ObjectivesTo investigate the association between Lactobacillus levels, depressive mood, and body mass index (BMI) among Chinese college students. In addition, to examine whether depressive mood mediates the association between Lactobacillus levels and BMI and whether physical activity (PA) moderates this association.MethodsThis cross-sectional study recruited 423 Chinese college students using a multi-stage stratified sampling method. Lactobacillus levels were measured from stool samples, depressive mood was assessed using a well-designed depression scale, PA was tracked with accelerometers, and BMI was calculated using calibrated electronic scales. Confirmatory factor analysis, correlation analysis, regression analysis, and tests for mediation and moderation effects were conducted using SPSS and AMOS software.ResultsLactobacillus levels exhibited significant negative correlations with depressive moods (r = −0.131, p < 0.01) and BMI (r = −0.113, p < 0.05), while depressive mood showed a positive correlation with BMI (r = 0.117, p < 0.05). Mediation analysis revealed that depressive moods mediated the association between Lactobacillus levels and BMI, with an indirect effect of −0.021 (95% CI: −0.062 to −0.001). PA significantly moderated the association between Lactobacillus levels and BMI, as evidenced by an interaction coefficient of 0.009 (p < 0.001).ConclusionDepressive mood could mediate the association between Lactobacillus levels and BMI, with PA playing a moderating role. This study provides new evidence for weight and depression management in college students.